2023
DOI: 10.3325/cmj.2023.64.307
|View full text |Cite
|
Sign up to set email alerts
|

Pathohistological features of the aging human lacrimal gland

Koraljka Hat,
Snježana Kaštelan,
Ana Planinić
et al.

Abstract: AimTo assess sex-related differences in the pathohistological features of the human lacrimal gland and to investigate age-related and sex-related differences in stereologically measured volume density of the secretory tissue, connective tissue, and fat. MethodsWe performed an observational analysis of acinar atrophy, periacinar fibrosis, periductal fibrosis, ductal dilation, ductal proliferation, fatty infiltration, and lymphocyte infiltration of hematoxylin and eosin-stained lacrimal gland samples from 81 cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Several studies have found that CDC family genes are associated with apoptosis 17 , which induces cellular senescence owing to its apoptotic mechanism, with the induction of cell senescence possibly resulting in numerous ocular surface disorders, including DED 18 . Simultaneously, cellular senescence, as one of the key causes of DED, is associated with alterations in the structure and function of the lachrymal gland, such as atrophy and reduced protein secretion 19 , with a higher probability of lacrimal gland lesions in older females 20 . The MCM gene family is widely found in eukaryotes such as humans, plays a role in regulating cell division, and is a key factor in initiating DNA replication 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that CDC family genes are associated with apoptosis 17 , which induces cellular senescence owing to its apoptotic mechanism, with the induction of cell senescence possibly resulting in numerous ocular surface disorders, including DED 18 . Simultaneously, cellular senescence, as one of the key causes of DED, is associated with alterations in the structure and function of the lachrymal gland, such as atrophy and reduced protein secretion 19 , with a higher probability of lacrimal gland lesions in older females 20 . The MCM gene family is widely found in eukaryotes such as humans, plays a role in regulating cell division, and is a key factor in initiating DNA replication 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Aging is a major risk factor for many eye diseases. As individuals age, they may experience increased susceptibility to DED due to alterations in the ocular surface, leading to a decrease in both tear production and lacrimal gland function [89]. In an aging group of rats, the lacrimal gland shows increased accumulation of lipofuscin-like substances, indicating age-related oxidative damage, while the levels of vitamin E, which has antioxidant capacity, are lower.…”
Section: Aging and Metabolic Disease Animal Modelsmentioning
confidence: 99%
“…Risk factors for DED include female gender, older age, pregnancy, postmenopausal estrogen therapy, thyroid disease, digital device usage, and contact lens wear. Other factors include refractive surgery, vitamin A deficiency, certain medications, and autoimmune and systemic diseases [ 3 , 4 , 7 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. The significance of DED is expected to rise in the future due to factors such as an aging population, environmental influences, and increased usage of digital devices [ 10 , 15 ].…”
Section: Introductionmentioning
confidence: 99%